2019
DOI: 10.1097/gme.0000000000001399
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of high-intensity interval training with combined training on physical function markers in obese postmenopausal women: a randomized controlled trial

Abstract: Objectives: This study compared the effects of high-intensity interval training (HIIT) with effects of combined training (CT) on physical function, body composition, and muscle strength in obese postmenopausal women (PW) (trial registration: NCT03200639). Methods: PW were randomized to CT (n = 12) and HIIT (n = 12). The CT group performed 30 minutes of moderate walking at 70% of maximum heart rate (MHR) and five resistance exercises at 70% of one repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…Of the 20 studies examining strength outcomes, 15 reported ≥1 strength parameter having been improved by HIIT compared to pre-training or compared to a moderate intensity continuous training (MICT) or non-exercise control. Of the remaining three (Robinson et al, 2017 ; Martins et al, 2018 ; Nunes et al, 2019 ), they all reported strength had improved more in a combined aerobic and resistance training group than a HIIT group.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Of the 20 studies examining strength outcomes, 15 reported ≥1 strength parameter having been improved by HIIT compared to pre-training or compared to a moderate intensity continuous training (MICT) or non-exercise control. Of the remaining three (Robinson et al, 2017 ; Martins et al, 2018 ; Nunes et al, 2019 ), they all reported strength had improved more in a combined aerobic and resistance training group than a HIIT group.…”
Section: Resultsmentioning
confidence: 98%
“…Of the 32 studies included, 14 were RCTs (Adamson et al, 2014 , 2020 ; Hwang et al, 2016 ; Coetsee and Terblanche, 2017 ; Sculthorpe et al, 2017 ; Aboarrage Junior et al, 2018 ; Malin et al, 2018 ; Martins et al, 2018 ; Ballesta-García et al, 2019 ; Hurst et al, 2019c ; Jiménez-García et al, 2019 ; Nunes et al, 2019 ; Taylor et al, 2019 ; Coswig et al, 2020 ), one was a quasi-experimental, non-randomized, single-blinded controlled study (Losa-Reyna et al, 2019 ), 16 were observational cohort studies (Bruseghini et al, 2015 , 2019 ; Boereboom et al, 2016 ; Guadalupe-Grau et al, 2017 ; Hayes et al, 2017 ; Herbert et al, 2017a , b ; Robinson et al, 2017 ; Wyckelsma et al, 2017 ; Andonian et al, 2018 ; Bartlett et al, 2018 ; Buckinx et al, 2018 , 2019 ; Søgaard et al, 2018 , 2019 ; Snijders et al, 2019 ), and one was a pilot study (although randomized; (Beetham et al, 2019 ) ( Table 1 ). Where a study had multiple outcome measures, they were examined separately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations